Lithium iron phosphate positive electrode material, preparation method and lithium ion battery

By adopting a hierarchical structure of lithium iron phosphate positive electrode material and combining with specific preparation methods, the shortcomings of lithium iron phosphate positive electrode material in low temperature and high power performance are solved, and good low temperature and high power performance are achieved.

CN116354323BActive Publication Date: 2025-02-11BYD CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111617440.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-27
Publication Date
2025-02-11
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

Lithium iron phosphate positive electrode material has shortcomings in low-temperature performance and power performance, and it is difficult to meet the requirements of power batteries for low-temperature operation and high-power requirements.

Method used

The lithium iron phosphate positive electrode material with a hierarchical structure containing a combination of sheet particles and granular particles is used, and the specific preparation method includes mixing iron sources, phosphorus sources, lithium sources and carbon sources, adding crystal surface guide agents, grinding and drying , sintering and crushing treatment to obtain the cathode material.

Benefits of technology

The lithium iron phosphate positive electrode material has a high temperature performance and significantly improved the low temperature performance and power performance, and can maintain a discharge efficiency of more than 65% under low temperature conditions of -20℃, and maintain a discharge efficiency of more than 78% under high power conditions of 15C. capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116354323B_ABST
    Figure CN116354323B_ABST
Patent Text Reader

Abstract

The embodiment of the present application provides a lithium iron phosphate positive electrode material, a preparation method and a lithium ion battery, wherein the lithium iron phosphate positive electrode material includes flaky particles and granular particles, wherein the number of flaky particles accounts for 15% to 45% of the total number of flaky particles and granular particles. The preparation method comprises: mixing an iron source, a phosphorus source, a lithium source and a carbon source uniformly and adding them to a dispersion medium for grinding to obtain a ground slurry; adding a crystal plane directing agent to the ground slurry, stirring uniformly and drying to obtain a precursor dry powder; sintering the precursor dry powder, and then coarsely crushing, screening and air flow pulverizing to obtain the lithium iron phosphate positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium-ion batteries. Specifically, the present application relates to a lithium iron phosphate positive electrode material, a preparation method and a lithium-ion battery. Background Art

[0002] In recent years, with my country's increasing efforts to promote new energy vehicles, environmentally friendly pure electric vehicles have become an inevitable trend in the future development of the automotive industry. They will gradually replace traditional fuel-powered buses and become the daily means of transportation for ordinary people. As the power source of electric vehicles, lithium-ion batteries have always been a focus of industry attention in terms of performance improvements.

[0003] Since their introduction, lithium-ion batteries have been highly sought after due to their high energy density, stable discharge voltage, and long operating life. As a crucial component of lithium-ion batteries, the choice of cathode material directly impacts their performance. Among common lithium-ion battery cathode materials, lithium iron phosphate (LIP) is widely used. LFP, with its orthorhombic olivine structure, exhibits exceptional cycle and high-temperature performance. However, its poor electronic and ionic conductivity results in poor low-temperature and power performance, making it difficult to meet the low-temperature and power requirements of power batteries.

[0004] In view of this, it is necessary to propose a preparation method of lithium iron phosphate positive electrode material to improve the low temperature performance and power performance of the lithium iron phosphate positive electrode material. Summary of the Invention

[0005] One purpose of the embodiments of the present application is to provide a new technical solution for a lithium iron phosphate positive electrode material, a preparation method, and a lithium-ion battery.

[0006] According to a first aspect of an embodiment of the present application, a lithium iron phosphate positive electrode material is provided, which includes flaky particles and granular particles, wherein the number of flaky particles accounts for 15% to 45% of the total number of flaky particles and granular particles.

[0007] Optionally, the number of the flaky particles accounts for 15% to 35% of the total number of the flaky particles and the granular particles.

[0008] Optionally, the average particle size of the shortest side of the flaky particles is 80 to 300 nm; and the average thickness of the flaky particles is 50 to 100 nm.

[0009] Optionally, the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is in the range of 1 to 3.

[0010] Optionally, the average particle size of the shortest side of the granular particles is 40 to 90 nm.

[0011] Optionally, the average aspect ratio of the granular particles is 1-4.

[0012] Optionally, the compaction density of the lithium iron phosphate positive electrode material is 2.0-2.2 g / cc.

[0013] According to a second aspect of an embodiment of the present application, a method for preparing the lithium iron phosphate positive electrode material as described in the first aspect is provided, the method comprising:

[0014] The iron source, phosphorus source, lithium source and carbon source are mixed uniformly and added into a dispersion medium for grinding to obtain a ground slurry;

[0015] Adding a crystal plane directing agent to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0016] The precursor dry powder is sintered, and then subjected to coarse crushing, screening and air flow pulverization to obtain the lithium iron phosphate positive electrode material.

[0017] Optionally, the iron source is at least one of anhydrous ferric phosphate, dihydrated ferric phosphate, ferric oxide, ferric chloride and ferric nitrate.

[0018] Optionally, the phosphorus source is at least one of phosphoric acid, ferric phosphate, ferric phosphate dihydrate, lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, ammonium dihydrogen phosphate and diamine hydrogen phosphate.

[0019] Optionally, the lithium source is at least one of lithium carbonate, lithium phosphate, lithium dihydrogen phosphate, lithium hydroxide and lithium nitrate.

[0020] Optionally, the carbon source is at least one of sucrose, water-soluble phenolic resin, glucose, polyethylene glycol, hydroxymethyl cellulose, polyacrylamide, starch, polyvinyl alcohol, highly conductive carbon tubes and graphene.

[0021] Optionally, the dispersion medium is at least one of deionized water, methanol, ethanol and N-methylpyrrolidone.

[0022] Optionally, the crystal plane director is at least one of magnesium chloride, magnesium nitrate, aluminum nitrate, zirconium nitrate, zirconium oxide, tetraethyl titanate, ethyl titanate, cobalt acetate, cobalt nitrate, vanadium pentoxide, ammonium metavanadate, manganese nitrate, manganese chloride, manganese sulfate, tungsten disulfide, tin chloride, tin oxide, molybdenum sulfide, niobium pentachloride and molybdenum oxide.

[0023] Optionally, the molar ratio of the iron source, phosphorus source and lithium source is 1:1:(1-1.05).

[0024] Optionally, the molar ratio of the iron source, phosphorus source and lithium source is 1:1:(1-1.03).

[0025] According to a third aspect of an embodiment of the present application, a lithium-ion battery is provided, characterized in that the lithium-ion battery includes the lithium iron phosphate positive electrode material as described in the first aspect.

[0026] One technical effect of the embodiments of the present application is:

[0027] An embodiment of the present application provides a lithium iron phosphate positive electrode material, which has a hierarchical structure comprising a combination of flaky particles and granular particles. The lithium iron phosphate positive electrode material has good high-temperature performance while also having excellent low-temperature performance and power performance.

[0028] Other features and advantages of the present application will become apparent from the following detailed description of exemplary embodiments of the present application with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the application and, together with the description, serve to explain the principles of the application.

[0030] Figure 1 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material obtained according to Example 1 of the present application;

[0031] Figure 2 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material obtained according to Example 2 of the present application;

[0032] Figure 3 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material obtained according to Example 3 of the present application;

[0033] Figure 4 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material obtained according to Example 4 of the present application. DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present application will now be described in detail with reference to the accompanying drawings. It should be noted that unless otherwise specifically stated, the relative arrangements of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present application.

[0035] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the present disclosure, its application, or uses.

[0036] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered part of the specification.

[0037] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0038] It should be noted that like reference numerals and letters refer to like items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0039] An embodiment of the present application provides a lithium iron phosphate positive electrode material, which includes flaky particles and granular particles, wherein the number of the flaky particles accounts for 15% to 45% of the total number of the flaky particles and the granular particles.

[0040] In the lithium iron phosphate positive electrode material provided in the embodiment of the present application, the combination of flaky particles and granular particles forms a hierarchical structure, wherein the flaky particles have a smaller specific surface area than the granular particles, so the presence of flaky particles is beneficial to reducing the occurrence of side reactions on the surface of the lithium iron phosphate positive electrode material, thereby improving its high-temperature storage performance and cycle performance; at the same time, since lithium ions are transmitted in a direction perpendicular to the flaky particles (i.e., along the thickness direction of the flaky particles), the transmission path is short, which does not affect the low-temperature performance and power performance of the lithium iron phosphate positive electrode material. Secondly, due to the presence of granular particles, their particle size is small and the lithium ion diffusion rate is fast, which is beneficial to improve the low-temperature performance and power performance of the lithium iron phosphate positive electrode material. Therefore, the higher the proportion of flaky particles, the better the high-temperature cycle performance and storage performance of the lithium iron phosphate positive electrode material; the higher the proportion of granular particles, the better the low-temperature performance and power performance of the lithium iron phosphate positive electrode material. In the lithium iron phosphate positive electrode material provided in the embodiment of the present application, the number of flaky particles is controlled to 15% to 45% of the total number, which can well balance the various properties of the lithium iron phosphate positive electrode material, so that it has excellent high-temperature cycle performance and storage performance while also having good low-temperature performance and power performance.

[0041] In one embodiment, further, the number of the flaky particles accounts for 15% to 35% of the total number of the flaky particles and the granular particles.

[0042] In this specific example, controlling the number of flaky particles to 15% to 35% of the total number can better balance the various properties of the lithium iron phosphate positive electrode material, so that it has excellent high-temperature cycle performance and storage performance while also having good low-temperature performance and power performance.

[0043] In one embodiment, further, the average particle size of the shortest side of the flaky particles is 80 to 300 nm; and the average thickness of the flaky particles is 50 to 100 nm.

[0044] In this specific example, when the average particle size of the shortest side of the flaky particles of the lithium iron phosphate positive electrode material is in the range of 80 to 300 nm, the processing performance of the lithium iron phosphate positive electrode material is relatively excellent.

[0045] When the thickness of the flaky particles is in the range of 50 to 100 nm, it is beneficial to shorten the diffusion path of lithium ions, increase the diffusion speed, and thus improve the low-temperature performance and power performance.

[0046] In one embodiment, further, the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is in the range of 1 to 3.

[0047] In this specific example, when the ratio of the average particle size of the longest side to the average particle size of the shortest side in the flaky particles is in the range of 1 to 3, the specific surface area can be reduced as much as possible while ensuring that the lithium ion diffusion path is short, thereby reducing the occurrence of surface side reactions and improving the high-temperature performance of the lithium iron phosphate positive electrode material.

[0048] In one embodiment, further, the average particle size of the shortest side of the granular particles is 40 to 90 nm.

[0049] In this specific example, when the average particle size of the shortest side of the granular particles is in the range of 40 to 90 nm, the particle size of the granular particles is smaller, so the diffusion rate of lithium ions is faster, which is beneficial to improving the low temperature performance and power performance of the lithium iron phosphate positive electrode material.

[0050] In one embodiment, further, the average aspect ratio of the granular particles is 1-4.

[0051] In this specific example, when the average aspect ratio of the granular particles is in the range of 1 to 4, the problems of low-temperature performance and power performance of the lithium iron phosphate positive electrode material caused by the excessively large aspect ratio can be reduced; and the crystal plane fracture that may occur during the charge and discharge cycle and expose new interfaces, thereby triggering the occurrence of new side reactions, can be avoided; at the same time, it is also beneficial to improve the high-temperature performance of the lithium iron phosphate positive electrode material.

[0052] In one embodiment, further, the compaction density of the lithium iron phosphate positive electrode material is 2.0-2.2 g / cc.

[0053] In this specific example, the compaction density of the lithium iron phosphate positive electrode material is in the range of 2.0-2.2 g / cc. Generally speaking, the compaction density and low-temperature performance and power performance show a negative correlation, that is, the greater the compaction density, the worse its low-temperature performance and power performance. Therefore, in this embodiment, the compaction density of the lithium iron phosphate positive electrode material is controlled within the range of 2.0-2.2 g / cc. Generally, the compaction density of the lithium iron phosphate positive electrode material obtained by the preparation method of the present application is in the range of 2.0-2.2 g / cc.

[0054] Lithium-ion battery lithium-ion battery lithium-ion battery lithium-ion battery lithium-ion battery

[0055] The present application also provides a method for preparing the lithium iron phosphate positive electrode material as described above, the method comprising:

[0056] S101, uniformly mixing an iron source, a phosphorus source, a lithium source, and a carbon source, and adding the mixture to a dispersion medium for grinding to obtain a ground slurry;

[0057] S102, adding a crystal plane directing agent to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0058] S103, sintering the precursor dry powder, and then coarsely crushing, screening and air flow milling to obtain the lithium iron phosphate positive electrode material.

[0059] The lithium iron phosphate positive electrode material obtained by the above-mentioned preparation method has the following characteristics: it presents a hierarchical structure comprising a combination of flaky particles and granular particles. The structural advantages of the lithium iron phosphate positive electrode material are: first, the flaky particles have a smaller specific surface area than the granular particles, so the presence of flaky particles is conducive to reducing the occurrence of side reactions on the surface of the lithium iron phosphate positive electrode material, thereby improving its high-temperature storage performance and cycle performance; at the same time, since lithium ions are transmitted in a direction perpendicular to the flaky particles (i.e., along the thickness direction of the flaky particles), the transmission path is short, which does not affect the low-temperature performance and power performance of the lithium iron phosphate positive electrode material. Secondly, due to the presence of granular particles, their particle size is smaller and the lithium ion diffusion rate is faster, which is conducive to improving the low-temperature performance and power performance of the lithium iron phosphate positive electrode material. In summary, the lithium iron phosphate positive electrode material has good high-temperature performance while also having excellent low-temperature performance and power performance.

[0060] In the preparation method of the lithium iron phosphate cathode material provided in the embodiments of the present application, a crystal plane director is introduced. In a specific dispersion medium, the crystal plane director can reduce the interfacial energy barrier of the crystal along the {010} crystal plane, thereby promoting the growth of the crystal along the {010} direction, and thus triggering the formation of flaky particles. At the same time, the resulting crystal rolling effect can prevent the agglomeration and growth of the particles. In addition, in the preparation method of the lithium iron phosphate cathode material provided in the embodiments of the present application, on the one hand, the particle size of the slurry after grinding is small, which increases the reactivity of the particles. On the other hand, the reduction of the interfacial energy barrier can promote the decrease of reaction energy. Then, through the drying process, the reaction of some crystals is induced in this process. As mentioned above, the crystals will preferentially grow along the {010} direction, resulting in the formation of flaky particles.

[0061] Furthermore, the amount of crystal plane director added will affect the number of flaky particles; in order to ensure that the number of flaky particles is controlled to be 15% to 45% of the total number, the amount of crystal plane director added in step S102 of the preparation method is 0.1% to 3% by mass.

[0062] In one embodiment, further, the iron source is at least one of anhydrous ferric phosphate, dihydrated ferric phosphate, ferric oxide, ferric chloride and ferric nitrate.

[0063] In one embodiment, further, the phosphorus source is at least one of phosphoric acid, ferric phosphate, ferric phosphate dihydrate, lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, ammonium dihydrogen phosphate and diamine hydrogen phosphate.

[0064] In one embodiment, further, the lithium source is at least one of lithium carbonate, lithium phosphate, lithium dihydrogen phosphate, lithium hydroxide and lithium nitrate.

[0065] In one embodiment, further, the carbon source is at least one of sucrose, water-soluble phenolic resin, glucose, polyethylene glycol, hydroxymethyl cellulose, polyacrylamide, starch, polyvinyl alcohol, highly conductive carbon tubes and graphene.

[0066] Furthermore, the added amount of the carbon source is 9% to 16%, and the added amount is based on the mass of the phosphorus source and iron source added above converted into iron phosphate.

[0067] In one embodiment, further, the dispersion medium is at least one of deionized water, methanol, ethanol and N-methylpyrrolidone.

[0068] In one embodiment, further, the crystal plane director is at least one of magnesium chloride, magnesium nitrate, aluminum nitrate, zirconium nitrate, zirconium oxide, tetraethyl titanate, ethyl titanate, cobalt acetate, cobalt nitrate, vanadium pentoxide, ammonium metavanadate, manganese nitrate, manganese chloride, manganese sulfate, tungsten disulfide, tin chloride, tin oxide, molybdenum sulfide, niobium pentachloride and molybdenum oxide.

[0069] In one embodiment, further, the molar ratio of the iron source, phosphorus source and lithium source is 1:1:(1-1.05). Further, the molar ratio of the iron source, phosphorus source and lithium source is 1:1:(1-1.03).

[0070] The grinding process described in step S101 is specifically ball milling or sand milling. The specific steps of the grinding process can be divided into coarse grinding and fine grinding. The zirconium balls used in the coarse grinding are 0.5-0.6 mm, and the zirconium balls used in the fine grinding are 0.05-0.3 mm. The grinding process is continuously carried out for 0.5-12 hours at a linear speed of 5-15 m / s.

[0071] The drying process in step S102 is either oven drying or belt drying.

[0072] The sintering process in step S103 is performed at a temperature of 650 to 760° C. for 5 to 10 hours.

[0073] The coarse crushing in step S103 is performed by mortar grinding or roller processing.

[0074] The principle of the air flow pulverization in step S103 is to apply air flow with a certain pressure to cause collisions between particles, so that the secondary particles formed by the agglomeration of primary particles are transformed into primary particles with better dispersion.

[0075] When the lithium iron phosphate obtained according to the preparation method of the present application is used as the positive electrode material of a lithium-ion battery, it shows excellent low-temperature performance, power performance, high-temperature performance and cycle performance. The excellent low-temperature performance refers to the lithium-ion battery being charged at room temperature and 0.5°C and then discharged at -20°C / 1C, with a discharge efficiency (discharge capacity / charge capacity) of up to 65% to 73%. The excellent power performance refers to the power of the lithium-ion battery at room temperature, and the discharge capacity at a 15C discharge rate is maintained at a rate of 78% to 83% compared to the discharge capacity at a 0.2C discharge rate. The excellent high-temperature performance refers to the capacity retention rate and capacity recovery rate of the lithium-ion battery when stored at 60°C; under storage conditions of 7 days, the capacity retention rate and capacity recovery rate are as high as 94% to 99% and 99% to 100% respectively. The excellent cycle performance refers to the capacity retention rate of the lithium-ion battery after 500 cycles at a 1C rate of 99%.

[0076] An embodiment of the present application further provides a lithium-ion battery, which includes the lithium iron phosphate positive electrode material as described above.

[0077] The present application is further described below through specific examples and comparative examples:

[0078] Example 1

[0079] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of deionized water for stirring. After stirring, the mixture was added to a coarse grinding device for coarse grinding for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0080] S102, adding 40 g of vanadium pentoxide to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0081] S103, then calcining the precursor dry powder at a temperature of 700 ° C for 8 hours, and then coarsely crushing, screening and air flow milling to obtain the lithium iron phosphate positive electrode material; Figure 1 As shown, the lithium iron phosphate cathode material exhibits a hierarchical structure composed of flaky particles and granular particles. The flaky particles account for 35% of the total material. The average particle size of the shortest side of the flaky particles is 162nm. The average thickness of the flaky particles is 90nm. The ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 2.5. The average particle size of the shortest side of the granular particles is 62nm, and the average aspect ratio of the granular particles is 1.8. The compacted density of the lithium iron phosphate cathode material is 2.01g / cc.

[0082] Example 2

[0083] S101, 0.5 kg of lithium phosphate, 0.96 kg of phosphoric acid, 1.0 kg of ferric oxide, and 200 g of glucose were mixed and added to 10 kg of deionized water for stirring. After stirring, the mixture was added to a coarse grinding device for coarse grinding for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0084] S102, adding 53 g of tin chloride to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0085] S103, then calcining the precursor dry powder at a temperature of 700 ° C for 8 hours, and then coarsely crushing, screening and air flow milling to obtain the lithium iron phosphate positive electrode material; Figure 2As shown, the lithium iron phosphate cathode material exhibits a hierarchical structure composed of flaky particles and granular particles. The flaky particles account for 40% of the total material. The average particle size of the shortest side of the flaky particles is 175nm. The average thickness of the flaky particles is 95nm. The ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 2.0. The average particle size of the shortest side of the granular particles is 66nm, and the average aspect ratio of the granular particles is 2.1. The compacted density of the lithium iron phosphate cathode material is 2.05g / cc.

[0086] Example 3

[0087] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0088] S102, adding 50 g of ethyl titanate to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0089] S103, then calcining the precursor dry powder at a temperature of 700 ° C for 8 hours, and then coarsely crushing, screening and air flow milling to obtain the lithium iron phosphate positive electrode material; Figure 3 As shown, the lithium iron phosphate cathode material exhibits a hierarchical structure composed of flaky particles and granular particles. The flaky particles account for 30% of the total material. The average particle size of the shortest side of the flaky particles is 145nm. The average thickness of the flaky particles is 82nm. The ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9. The average particle size of the shortest side of the granular particles is 55nm, and the average aspect ratio of the granular particles is 1.6. The compacted density of the lithium iron phosphate cathode material is 2.03g / cc.

[0090] Example 4

[0091] S101, 0.5 kg of lithium phosphate, 0.96 kg of phosphoric acid, 1.0 kg of ferric oxide, and 200 g of glucose were mixed and added to 10 kg of methanol for stirring. After stirring, the mixture was added to a coarse grinding device for coarse grinding for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0092] S102, adding 53 g of niobium pentachloride to the ground slurry, stirring evenly, and then drying to obtain a precursor dry powder;

[0093] S103, then calcining the precursor dry powder at a temperature of 700 ° C for 8 hours, and then coarsely crushing, screening and air flow milling to obtain the lithium iron phosphate positive electrode material; Figure 4 As shown, the lithium iron phosphate cathode material exhibits a hierarchical structure composed of flaky and granular particles. The flaky particles account for 37% of the total material. The average particle size of the shortest side of the flaky particles is 168nm. The average thickness of the flaky particles is 92nm. The ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 2.2. The average particle size of the shortest side of the granular particles is 64nm, and the average aspect ratio of the granular particles is 1.9. The compacted density of the lithium iron phosphate cathode material is 2.12g / cc.

[0094] Example 5

[0095] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0096] S102, adding 10 g of niobium pentachloride to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0097] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 15%; the average particle size of the shortest side of the flaky particles is 168nm; the average thickness of the flaky particles is 92nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 2.2; the average particle size of the shortest side of the granular particles is 64nm, and the average aspect ratio of the granular particles is 1.9; the compacted density of the lithium iron phosphate positive electrode material is 2.16g / cc.

[0098] Example 6

[0099] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0100] S102, adding 100 g of niobium pentachloride to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0101] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 45%; the average particle size of the shortest side of the flaky particles is 168nm; the average thickness of the flaky particles is 92nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 2.2; the average particle size of the shortest side of the granular particles is 64nm, and the average aspect ratio of the granular particles is 1.9; the compacted density of the lithium iron phosphate positive electrode material is 2.02g / cc.

[0102] Example 7

[0103] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0104] S102, adding 92 g of ethyl titanate to the ground slurry, stirring evenly, and then drying to obtain a precursor dry powder;

[0105] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 80nm; the average thickness of the flaky particles is 82nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9; the average particle size of the shortest side of the granular particles is 55nm, and the average aspect ratio of the granular particles is 1.6; the compacted density of the lithium iron phosphate positive electrode material is 2.03g / cc.

[0106] Example 8

[0107] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0108] S102, adding 15 g of ethyl titanate to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0109] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 300nm; the average thickness of the flaky particles is 82nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9; the average particle size of the shortest side of the granular particles is 55nm, and the average aspect ratio of the granular particles is 1.6; the compacted density of the lithium iron phosphate positive electrode material is 2.18g / cc.

[0110] Example 9

[0111] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0112] S102, adding 115 g of ethyl titanate to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0113] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 170nm; the average thickness of the flaky particles is 50nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9; the average particle size of the shortest side of the granular particles is 55nm, and the average aspect ratio of the granular particles is 1.6; the compacted density of the lithium iron phosphate positive electrode material is 2.04g / cc.

[0114] Example 10

[0115] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0116] S102, adding 20 g of ethyl titanate to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0117] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 170nm; the average thickness of the flaky particles is 100nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9; the average particle size of the shortest side of the granular particles is 55nm, and the average aspect ratio of the granular particles is 1.6; the compacted density of the lithium iron phosphate positive electrode material is 2.17g / cc.

[0118] Example 11

[0119] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0120] S102, adding 32 g of ethyl titanate to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0121] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 170nm; the average thickness of the flaky particles is 75nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.0; the average particle size of the shortest side of the granular particles is 55nm, and the average aspect ratio of the granular particles is 1.6; the compacted density of the lithium iron phosphate positive electrode material is 2.10g / cc.

[0122] Example 12

[0123] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0124] S102, adding 36 g of ammonium metavanadate to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0125] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 170nm; the average thickness of the flaky particles is 75nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 3.0; the average particle size of the shortest side of the granular particles is 55nm, and the average aspect ratio of the granular particles is 1.6; the compacted density of the lithium iron phosphate positive electrode material is 2.16g / cc.

[0126] Example 13

[0127] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0128] S102, adding 134 g of vanadium pentoxide to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0129] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 170nm; the average thickness of the flaky particles is 75nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9; the average particle size of the shortest side of the granular particles is 40nm, and the average aspect ratio of the granular particles is 1.6; the compacted density of the lithium iron phosphate positive electrode material is 2.05g / cc.

[0130] Example 14

[0131] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0132] S102, adding 20 g of vanadium pentoxide to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder;

[0133] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 170nm; the average thickness of the flaky particles is 75nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9; the average particle size of the shortest side of the granular particles is 90nm, and the average aspect ratio of the granular particles is 1.6; the compacted density of the lithium iron phosphate positive electrode material is 2.18g / cc.

[0134] Example 15

[0135] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0136] S102, adding 85 g of niobium pentachloride to the ground slurry, stirring evenly, and then drying to obtain a precursor dry powder;

[0137] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 170nm; the average thickness of the flaky particles is 75nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9; the average particle size of the shortest side of the granular particles is 65nm, and the average aspect ratio of the granular particles is 4.0; the compacted density of the lithium iron phosphate positive electrode material is 2.03g / cc.

[0138] Example 16

[0139] S101, 0.93 kg of lithium carbonate, 3.75 kg of iron phosphate, and 70 g of sucrose were mixed and added to 10 kg of ethanol and stirred. After stirring, the mixture was added to a coarse grinding device and coarsely ground for 30 minutes, and then sand-milled in a fine grinding mill at a linear speed of 10 m / s for 2 hours to obtain a ground slurry;

[0140] S102, adding 16 g of niobium pentachloride to the ground slurry, stirring evenly, and then drying to obtain a precursor dry powder;

[0141] S103. The precursor dry powder is then calcined at 700°C for 8 hours, and then subjected to coarse crushing, sieving and air flow milling to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material exhibits a hierarchical structure morphology composed of a combination of flaky particles and granular particles. The number of flaky particles accounts for 30%; the average particle size of the shortest side of the flaky particles is 170nm; the average thickness of the flaky particles is 75nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is 1.9; the average particle size of the shortest side of the granular particles is 65nm, and the average aspect ratio of the granular particles is 1.0; the compacted density of the lithium iron phosphate positive electrode material is 2.14g / cc.

[0142] Comparative Example 1

[0143] Compared with Example 3, the difference is that the mass of the added ethyl titanate is 300 g, and the other conditions are the same; the prepared lithium iron phosphate positive electrode material basically only contains flaky particles.

[0144] Comparative Example 2

[0145] Compared with Example 1, the difference is that vanadium pentoxide is not added, and other conditions are the same; the prepared lithium iron phosphate positive electrode material only contains granular particles.

[0146] Comparative Example 3

[0147] Compared with Example 3, the difference is that the mass of added ethyl titanate is 6 g, and the other conditions are the same; the prepared lithium iron phosphate positive electrode material contains flaky particles and granular particles, of which the number of flaky particles accounts for 5%.

[0148] Comparative Example 4

[0149] Compared with Example 3, the difference is that the mass of the added ethyl titanate is 230 g, and the other conditions are the same; the prepared lithium iron phosphate positive electrode material contains flaky particles and granular particles, of which the number of flaky particles accounts for 60%.

[0150] Comparative Example 5

[0151] The lithium iron phosphate positive electrode material includes flaky particles and granular particles, wherein the compaction density of the lithium iron phosphate positive electrode material is 2.43 g / cc.

[0152] Electrochemical performance test

[0153] The lithium iron phosphate cathode materials obtained in Examples 1 to 16 and Comparative Examples 1 to 5 were respectively made into lithium ion batteries, and the following electrochemical performance tests were performed on the lithium ion batteries:

[0154] 1) Low-temperature capacity retention test: The lithium-ion battery is charged at room temperature at a rate of 0.1C with a constant current to 3.8V, then charged at a constant voltage at 3.8V until the current reaches 0.1C. It is then discharged at a constant current to 2.5V at 0.1C. This cycle is repeated once, followed by a constant current charge at a rate of 0.5C to 3.8V, and then a constant voltage charge at 3.8V until the current reaches 0.1C. The lithium-ion battery is placed in a -20°C freezer and discharged at a rate of 1C with a constant current to 2.0V. The ratio of the discharge capacity at -20°C to the charge capacity at room temperature at 0.5C is the low-temperature capacity retention of the lithium-ion battery. The test results are shown in Table 1 below.

[0155] Table 1:

[0156] Examples / Comparative Examples -20℃ low temperature capacity retention Example 1 69% Example 2 65% Example 3 71% Example 4 67% Example 5 68% Example 6 65% Example 7 71.5% Example 8 69.5% Example 9 72.1% Example 10 70.1% Example 11 71.5% Example 12 66.5% Example 13 71.6% Example 14 67.9% Example 15 68% Example 16 72% Comparative Example 1 56% Comparative Example 2 61% Comparative Example 3 62% Comparative Example 4 64% Comparative Example 5 40%

[0157] As can be seen from Table 1, the low-temperature capacity retention rates of the lithium-ion batteries corresponding to Examples 1 to 16 at -20°C are as low as 65% (Examples 2 and 6); the low-temperature capacity retention rates of the lithium-ion batteries corresponding to Comparative Examples 1 to 5 at -20°C are as high as 64% (Comparative Example 4). This shows that the lithium-ion batteries corresponding to the Examples have superior low-temperature capacity retention rates at -20°C compared to the lithium-ion batteries corresponding to the Comparative Examples.

[0158] 2) Discharge Capacity Retention Test: The lithium-ion battery was charged to 3.8 V by CCCV at a rate of 0.2C with a cutoff current of 0.02C; then CC discharged to 2.5 V at a rate of 15C. The ratio of the discharge capacity at the rate of 15C to the discharge capacity at the rate of 0.2C was the discharge capacity retention rate at the rate of 15C. The test results are shown in Table 2 below.

[0159] Table 2:

[0160]

[0161]

[0162] As can be seen from Table 2, the discharge capacity retention rate at a rate of 15C for the lithium-ion batteries corresponding to Examples 1 to 16 is as low as 78% (Example 6); the discharge capacity retention rate at a rate of 15C for the lithium-ion batteries corresponding to Comparative Examples 1 to 5 is as high as 76.2% (Comparative Example 4). This shows that the lithium-ion batteries corresponding to the examples have a superior discharge capacity retention rate at a rate of 15C compared to the lithium-ion batteries corresponding to the comparative examples.

[0163] 3) High-temperature storage capacity recovery rate test: The lithium-ion battery was fully charged at 0.1 CCCV, then stored in a 60°C oven for 7 days. After being taken out, the battery was discharged to 2.5V at 0.1C, then charged to 3.8V at 0.1 CCCV, and then discharged to 2.5V. The ratio of the first discharge capacity of the lithium-ion battery after high-temperature storage to the discharge capacity before storage is the capacity residual rate, and the ratio of the discharge capacity of the subsequent cycle to the discharge capacity before storage is the high-temperature storage capacity recovery rate of the lithium-ion battery. The test results are shown in Table 3 below.

[0164] Table 3:

[0165]

[0166]

[0167] It can be concluded from Table 3 that the capacity remaining rate of the lithium ion batteries corresponding to Examples 1 to 16 at 60°C and 7 days is as low as 95.2% (Example 2), and the capacity remaining rate of the lithium ion batteries corresponding to Comparative Examples 1 to 5 at 60°C and 7 days is as high as 95.1% (Comparative Example 1 and Comparative Example 2); the high-temperature storage capacity recovery rate of the lithium ion batteries corresponding to Examples 1 to 16 at 60°C and 7 days is as low as 98.5% (Example 7 and Example 16), and the high-temperature storage capacity recovery rate of the lithium ion batteries corresponding to Comparative Examples 1 to 5 at 60°C and 7 days is as high as 98.3% (Comparative Example 1). It can be seen that the lithium ion batteries corresponding to the embodiments are superior to the lithium ion batteries corresponding to the comparative examples in terms of the capacity remaining rate at 60°C and 7 days and the high-temperature storage capacity recovery rate at 60°C and 7 days.

[0168] 4) Cycle Capacity Retention Test: Under normal temperature conditions and at a 1C rate, after a lithium-ion battery undergoes 500 charge and discharge cycles, the ratio of the capacity at the 500th cycle to the capacity at the first cycle is the cycle capacity retention rate of the lithium-ion battery. The test results are shown in Table 4 below.

[0169] Table 4:

[0170] Examples / Comparative Examples 1C, 500 cycles capacity retention rate Example 1 99.2% Example 2 99.0% Example 3 99.5% Example 4 99.1% Example 5 99.0% Example 6 99.3% Example 7 99.4% Example 8 99.6% Example 9 99.0% Example 10 99.6% Example 11 96.9% Example 12 99.6% Example 13 99.1% Example 14 99.5% Example 15 99.6% Example 16 97.8% Comparative Example 1 95.1% Comparative Example 2 91.1% Comparative Example 3 92.2% Comparative Example 4 94.1% Comparative Example 5 93.6%

[0171] As can be seen from Table 4, the lithium-ion batteries corresponding to Examples 1 to 16 have a lowest capacity retention rate of 96.9% (Example 11) at 1C and 500 cycles, while the lithium-ion batteries corresponding to Comparative Examples 1 to 5 have a highest capacity retention rate of 95.1% (Comparative Example 1) at 1C and 500 cycles. This shows that the lithium-ion batteries corresponding to the Examples have a superior capacity retention rate at 1C and 500 cycles compared to the lithium-ion batteries corresponding to the Comparative Examples.

[0172] Although some specific embodiments of the present application have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present application. It should be understood by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present application. The scope of the present application is defined by the appended claims.

Claims

1. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material includes flaky particles and granular particles, wherein the number of the flaky particles accounts for 15% to 35% of the total number of the flaky particles and the granular particles; The average particle size of the shortest side of the flaky particles is 170~300nm; the average thickness of the flaky particles is 50~75nm; the ratio of the average particle size of the longest side to the average particle size of the shortest side of the flaky particles is in the range of 1~3; the average particle size of the shortest side of the granular particles is 40~65nm; the average aspect ratio of the granular particles is 1~1.6; the compaction density of the lithium iron phosphate positive electrode material is 2.0-2.2g / cc.

2. A method for preparing the lithium iron phosphate positive electrode material as claimed in claim 1, characterized in that: The method comprises: The iron source, phosphorus source, lithium source and carbon source are uniformly mixed and added into a dispersion medium for grinding to obtain a ground slurry; Adding a crystal plane directing agent to the ground slurry, stirring evenly and then drying to obtain a precursor dry powder; The precursor dry powder is sintered, and then coarsely crushed, screened and air flow crushed to obtain the lithium iron phosphate positive electrode material; the lithium iron phosphate positive electrode material includes flaky particles and granular particles, wherein the number of the flaky particles accounts for 15% to 35% of the total number of the flaky particles and the granular particles.

3. The method for preparing the lithium iron phosphate positive electrode material according to claim 2, characterized in that: The iron source is at least one of anhydrous ferric phosphate, dihydrated ferric phosphate, ferric oxide, ferric chloride and ferric nitrate.

4. The method for preparing the lithium iron phosphate positive electrode material according to claim 2, characterized in that: The phosphorus source is at least one of phosphoric acid, iron phosphate, iron phosphate dihydrate, lithium phosphate, lithium dihydrogen phosphate, lithium monohydrogen phosphate, ammonium dihydrogen phosphate and diamine hydrogen phosphate.

5. The method for preparing the lithium iron phosphate positive electrode material according to claim 2, characterized in that: The lithium source is at least one of lithium carbonate, lithium phosphate, lithium dihydrogen phosphate, lithium hydroxide and lithium nitrate.

6. The method for preparing a lithium iron phosphate positive electrode material according to claim 2, characterized in that: The carbon source is at least one of sucrose, water-soluble phenolic resin, glucose, polyethylene glycol, hydroxymethyl cellulose, polyacrylamide, starch, polyvinyl alcohol, highly conductive carbon tubes and graphene.

7. The method for preparing a lithium iron phosphate positive electrode material according to claim 2, characterized in that: The dispersion medium is at least one of deionized water, methanol, ethanol and N-methylpyrrolidone.

8. The method for preparing a lithium iron phosphate positive electrode material according to claim 2, characterized in that: The crystal plane director is at least one of magnesium chloride, magnesium nitrate, aluminum nitrate, zirconium nitrate, zirconium oxide, tetraethyl titanate, ethyl titanate, cobalt acetate, cobalt nitrate, vanadium pentoxide, ammonium metavanadate, manganese nitrate, manganese chloride, manganese sulfate, tungsten disulfide, tin chloride, tin oxide, molybdenum sulfide, niobium pentachloride and molybdenum oxide.

9. The method for preparing a lithium iron phosphate positive electrode material according to claim 2, characterized in that: The molar ratio of the iron source, phosphorus source and lithium source is 1:1:(1-1.05).

10. The method for preparing a lithium iron phosphate positive electrode material according to claim 9, characterized in that: The molar ratio of the iron source, phosphorus source and lithium source is 1:1:(1-1.03).

11. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron phosphate positive electrode material as claimed in claim 1.

Citation Information

Patent Citations

  • Low-temperature preparation method of nano flaky lithium iron phosphate particles

    CN110436432A

  • Lithium iron phosphate positive pole piece and preparation method and application thereof

    CN113422049A